Market Value Equity Model dari Pengakuan dan Pengungkapan Akuntansi Pensiun pada Perusahaan di Indonesia - Nina Novitafiani; Deliany Deliany (Faculty of Economics, Universitas Internasional Batam, 2018)
This study aims to investigate the value relevance of pension accounting recognition and disclosure using market equity value models in companies in Indonesia after IFRS convergence. The focus of this study on companies in Indonesia which is one of the countries that conduct IFRS convergence including IAS 19 is converged in PSAK 24 and IAS 26 in PSAK 18. Recognition and disclosure have different value relevance for investors. Based on PSAK 18 and PSAK 24, accounting for pensions are in off-balance-sheet so it is likely to be useful for decision making for investors. This research is a field study on companies listed onthe Indonesia Stock Exchange (IDX) using company financial statements that disclose pension accounting. With a sample of 200 listed companies for 2012 until 2017, data analysis techniques in this study use two step approach regression with institutional ownership moderation variables. The results show that the relevance of the value of disclosure (PSAK 18) is higher than recognition (PSAK 24). Based on more detailed report, investors can measure that theallowance for assets for pension liabilities does not exceed the company's ability, and makes it easier for investors to measure profits and losses from pension investments.